Rickets and Vitamin D Deficiency in Alaska Native Children - Singleton, Rosalyn; Lescher, Rachel; Gessner, Bradford D.; Benson, Matthew; Bulkow, Lisa; Rosenfeld, John; Thomas, Timothy; Holman, Robert C.; Haberling, Dana; Bruce, Michael; Bartholomew, Michael; Tiesinga, James
Background Rickets and vitamin D deficiency appeared to increase in Alaskan children, starting in the 1990s. We evaluated the epidemiology of rickets and vitamin D deficiency in Alaska Native (AN) children in 2001-2010. Methods We analyzed 2001-2010 visits with rickets or vitamin D deficiency diagnosis for AN and American Indian children and the general U.S. population aged <10 years. We conducted a case-control study of AN rickets/vitamin D deficient cases and age- and region-matched controls. Results AN children annual rickets-associated hospitalization rate (2.23/100,000 children/year) was higher than general U.S. rate (1.23; 95% CI 1.08-1.39). Rickets incidence increased with latitude. Rickets/vitamin D deficiency cases were more likely to have malnutrition (OR 38.1; 95% CI 4.9-294), had similar breastfeeding prevalence, and were less likely to have received vitamin D supplementation (OR 0.23; 95% CI 0.1-0.87), than controls. Conclusions Our findings highlight the importance of latitude, malnutrition and lack of vitamin D supplementation as risk factors for rickets. CC999999/Intramural CDC HHS/United States 2016-07-01T00:00:00Z 25741788 PMC4678029